JCMT 2021
DOI: 10.20517/2394-4722.2020.118
|View full text |Cite
|
Sign up to set email alerts
|

Role of 18F-FDG PET/CT in detection of hematogenous metastases of advanced differentiated thyroid carcinoma: a systematic review and meta-analysis

Abstract: How to cite this article: Quartuccio N, Rubello D. Role of 18 F-FDG PET/CT in detection of hematogenous metastases of advanced differentiated thyroid carcinoma: a systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Beta-emitting radionuclides encompass Phosphorus-32 ( 32 P), Strontium-89 ( 89 Sr), Renium-186 and -188 ( 186 Re, 188 Re), Samarium-153 ( 153 Sm), Selenium-117m ( 117m Sn), and Lutetium-177 ( 177 Lu) ( 29 ). Apart from these, a special mention is needed for 131 I, whose use against BMs has been limited in patients with thyroid cancer ( 30 ). Conversely, alpha-emitting therapy currently relies primarily on the clinical use of Radium-223 ( 223 Ra).…”
Section: Resultsmentioning
confidence: 99%
“…Beta-emitting radionuclides encompass Phosphorus-32 ( 32 P), Strontium-89 ( 89 Sr), Renium-186 and -188 ( 186 Re, 188 Re), Samarium-153 ( 153 Sm), Selenium-117m ( 117m Sn), and Lutetium-177 ( 177 Lu) ( 29 ). Apart from these, a special mention is needed for 131 I, whose use against BMs has been limited in patients with thyroid cancer ( 30 ). Conversely, alpha-emitting therapy currently relies primarily on the clinical use of Radium-223 ( 223 Ra).…”
Section: Resultsmentioning
confidence: 99%
“…The difference in terms of DR of these two instrumental examinations might underlie the variable diagnostic accuracy of [ 18 F]FDG PET in DTC, which is affected by several different clinical and histological features ( 40 42 ); however, since none of the included studies assessed the differences in diagnostic accuracy of both examinations based on histologic variants and clinical features; it is not feasible to validate this hypothesis. In this setting, it is noteworthy that [ 18 F]FDG has a valuable diagnostic performance in DTC patients with hematogenous metastases, as stated in a recent meta-analysis of literature ( 43 ); unfortunately, it is currently not feasible to make an indirect comparison of these two imaging techniques since the data gathered in this systematic review does not allow to pool the diagnostic accuracies reported in the included studies. More studies are needed in this setting to assess which patients might benefit from FAP-targeted imaging rather than [ 18 F]FDG PET.…”
Section: Discussionmentioning
confidence: 97%
“…Anaplastic thyroid cancer (ATC) is still a rapidly deadly tumor without any established therapy. Lee and Cheng [5] present elegant studies of transcriptional pathways to explain transcriptional addiction that makes this tumor so difficult to treat effectively. They propose the use of small molecule inhibitors to target the transcriptional regulators in ATC.…”
Section: Davidson and Carrmentioning
confidence: 99%